Analisis uji efektivitas lkpd virtual laboratory pada materi medan, induksi, dan gaya magnetik serta fenomena induksi elektromagnetik kelas XII SMAN 5 Padang - Yolvi Oktaviani; Masril Masril; Yenni Darvina; Hidayati Hidayati (PILLAR OF PHYSICS EDUCATION, 2019)
This research is motivated by the low physical competence of students, one of the reason is the practical activities that have not been optimally carried out in schools, because of limited tools and time, are carried out using virtual LKPD. This study aims to analyze the effectiveness of the LKPD virtual laboratory on the achievement of competence of students in class XII SMAN 5 Padang. This research is classified as quasi experimental design by method pretest-posttest control group design. Samples from all class XII students were determined using purposive sampling technique. The data of this study only focused on the achievement of knowledge competencies obtained through the pretest and posttest in the experimental class to see the effectiveness of the use of teaching materials carried out using the t-correlation test. Data on the achievement of knowledge competencies were also analyzed to see differences in learning outcomes of the experimental class and the control class using the two average similarity test. Based on the result of the data analysis the value obtained t count < t table . This shows that the virtual laboratory base ICT is effectively used in physics learning class XII at SMAN 5 Padang. Based on the posttest result of the two sample classes using two similarity test on average at the level of α = 0,05 obtained t count > t table .Based on the analysis of the two sample classes it can be concluded that there are differences in the learning outcomes of the experimental class using the virtual laboratory LKPD.